Efforts to Increase Curiosity Through Cooperative Lectures Type Student Teams Achievement Division (STAD) with Guided Discovery Approach in Economics Mathematics Course - Indah Pertiwi (IJESS International Journal of Education and Social Science, 2023)
The objectives of this study include: (1) To determine the implementation of cooperative lectures of the Student Teams Achievement Division (STAD) type with a guided discovery approach in the economic mathematics course of students of the D3 Accounting Study Program, Pamulang University, (2) To determine the results of the improvement curiosity in the application of cooperative lectures of the Student Teams Achievement Division (STAD) type with a guided discovery approach in the mathematical economics course of students of the D3 Accounting Study Program, Pamulang University, and (3) To find out the obstacles faced by lecturers and students as well as the efforts made in the application of cooperative lectures of the Student Teams Achievement Division (STAD) type with a guided discovery approach in economic mathematics courses for students of the D3 Accounting Study Program, Pamulang University. Research on efforts to increase curiosity through STAD type cooperative learning with a guided discovery approach in economics mathematics courses is a type of Classroom Action Research. This Classroom Action Research is intended to overcome a problem or improve a learning in the classroom. Therefore, the purpose of this research is to change the initial situation or condition to the expected condition (improvement oriented). Based on the results of research and discussion, it is concluded that learning mathematics using the STAD type cooperative model with a guided discovery approach can increase the curiosity of D3 Accounting students at Pamulang University. Learning mathematics using the STAD type cooperative model with a guided discovery approach at the D3 Accounting at Pamulang University has been carried out according to the procedure. The implementation of mathematics learning using the STAD type cooperative model with a guided discovery approach has been carried out following the steps that have been set.